Comparative analysis of cattle production systems in Nigeria grassland agroecology - Akeem B. Sikiru; Bisong O. Otu; Olayinka J. Makinde; Saoban Saheed; Stephen S. A. Egena; Ibrahim R. Muhammad (Circular Agricultural Systems)
This study explores herd production characteristics and phenotypic traits of indigenous dairy cattle in the grassland agroecology of Nigeria. The study highlighted the crucial role of agroecology as a modifier of cattle production operations and emphasized the need for further research to understand the genetic basis of variations in the production. Herd production data were collected through focus group meetings using FEAST software, while body measurements and phenotypic traits of lactating and breeding cattle were recorded in the agroecological zone within the grassland. The data obtained were subjected to descriptive statistics, and Moses Test of Extreme Reaction using SPSS v.20.0.0. The results indicate that the agroecology type significantly influenced various herd production characteristics (p < 0.05). Additionally, agroecology had a significant effect on body measurements and phenotypic trait expressions in the cattle, including live weight, body condition score, testis circumference, age at puberty, and age at first calving (p < 0.05). Furthermore, age differences were observed among cows based on the agroecological zones (p = 0.008), while no significant variation was found in the age of breeding bulls across both agroecology. This study concludes that within the Nigeria's grassland, agroecology plays a crucial role as a modifier of herd production characteristics and phenotypic trait expressions in smallholder dairy cattle operations. These cannot be unconnected with genetics, hence, there is a need for understanding the genetic basis of the variations.